Developing Linguistic Competence through Multimodal Digital Information Systems – Insights from English Philology - Kholodniak, Olena (Indian Journal of Information Sources and Services, 2025)
This article investigates the integration of multimodal approaches, conceptualized as interactive learning systems, for developing linguistic competence crucial for effective engagement with contemporary digital information sources and services. Examining language as a dynamic system of signs within a digitally saturated environment, it is argued that a multimodal framework—which thoughtfully combines visual, auditory, and textual elements delivered via information technologies—can significantly enhance users’ understanding and proficiency in processing complex information. The study analyzes effective pedagogical strategies that leverage multimodal resources and interactive digital platforms to facilitate deeper engagement with linguistic concepts, thereby improving the ability to interpret and create multimodal digital content. Through a comprehensive empirical assessment involving pre/post-tests, surveys, case studies, and focus groups within an English philology context, the advantages of multimodal learning environments (as information systems) in fostering critical linguistic skills (syntax, semantics, pragmatics) are underscored. These skills are foundational for advanced digital information literacy. The findings indicate statistically significant improvements in linguistic components and user engagement when multimodal strategies are employed. The implications of these approaches for designing effective educational information systems and training users to critically navigate a rapidly evolving multimodal information landscape are discussed. This research contributes to the discourse on innovative methodologies for developing information competence, advocating for a comprehensive approach that reflects the intricacies of contemporary digital information use and design.